Avaliação de método de diagnóstico diferencial e da suscetibilidade de Pythium insidiosum frente a antimicrobianos de uso tópico e sistêmico - Itaqui, Sabrina Rosa (2016)
Pythiosis is an infection caused by the oomycete Pythium insidiosum that lacks studies aimed at their rapid identification and determination of effective antimicrobial therapy. In this context, this work aimed a) to evaluate the in vitro antimicrobial properties of the topical antimicrobials benzalkonium, cetrimide, cetylpyridinium, mupirocin and triclosan against P. insidiosum and the potential synergism of these compounds with azithromycin or terbinafine and; b) to determine the potential of the presumptive identification of P. insidiosum cultures based on mycelial inhibition caused by disks containing antibacterial drugs recognized for its antimicrobial properties against P. insidiosum. Through the susceptibility tests performed according to the M38-A2 protocol from CLSI with inoculum consisting of zoospores of P. insidiosum, it was observed that all topical antimicrobials, except potassium permanganate (MIC > 64 μg/mL) inhibited the in vitro growth of clinical isolates of P. insidiosum in concentrations ranging from 0.5 to 32 μg/mL. Most interactions observed through the checkerboard technique were indifferent when terbinafine (60% indifferent interactions) or azithromycin (80% indifferent interactions) were associated with topical antimicrobials. Only the combination cetylpyridinium + terbinafine resulted in relevant synergistic interactions (71.4%). The evaluation of the presumptive identification of P. insidiosum with antibacterial drugs used cultures P. insidiosum in Sabouraud dextrose agars and Muller Hinton in the presence of disks containing antibacterial placed at 1.5 cm away from the mycelial growth. These tests showed that the presumptive identification of P. insidiosum is dependent on the culture media used. On Sabouraud dextrose agar, azithromycin and clarithromycin allowed the identification of 100% of the isolates, and the same was observed for the use of mupirocin in Muller Hinton agar. The minocycline was the only antibacterial agent that allowed the identification of 100% of the strains in both culture media. The results described in this work suggest new topical therapies and new diagnostic approaches that can support future in vitro and in vivo works using a larger and diverse number of clinical isolates of P. insidiosum.